SELECTION OF CULTURAL CODES IN ARTISTIC TEXTS: METHODS AND APPROACHES - Myronova, Natalia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article is dedicated to the analysis of methods and approaches to selecting cultural codes in literature. It examines semiotic, linguistic, contextual, and intertextual analysis as key methodologies that help uncover the deep layers of cultural consciousness and identity embedded in artistic texts. The necessity of studying cultural codes for understanding socio-historical realities and fostering cultural literacy is discussed. ____________ References: • Bakhtin, M. M. (1981). The Dialogic Imagination: Four Essays. (C. Emerson & M. Holquist, Trans.). University of Texas Press. • Bakhtin, M. M. (1984). Rabelais and His World. (H. Iswolsky, Trans.). Indiana University Press. • Barthes, R. (1967). Elements of Semiology. (A. Lavers & C. Smith, Trans.). Hill and Wang. • Barthes, R. (1970). S/Z. Paris: Seuil. • Barthes, R. (1977). Image-Music-Text. (S. Heath, Trans.). Hill and Wang. • Gadamer, H.-G. (1975). Truth and Method. (J. Weinsheimer & D. G. Marshall, Trans.). Continuum. • Gadamer, H.-G. (2004). Philosophical Hermeneutics. (D. E. Linge, Trans.). University of California Press. • Genette, G. (1980). Narrative Discourse: An Essay in Method. (J. E. Lewin, Trans.). Cornell University Press. • Genette, G. (1997). Paratexts: Thresholds of Interpretation. (J. E. Lewin, Trans.). Cambridge University Press. • Greimas, A. J. (1983). Structural Semantics: An Attempt at a Method. (D. McDowell, R. Schleifer, & A. Velie, Trans.). University of Nebraska Press. • Greimas, A. J. (1987). On Meaning: Selected Writings in Semiotic Theory. (P. Perron & F. H. Collins, Trans.). University of Minnesota Press. • Lakoff, G. (1980). Metaphors We Live By. (with M. Johnson). University of Chicago Press. • Lakoff, G. (1987). Women, Fire, and Dangerous Things: What Categories Reveal About the Mind. University of Chicago Press. • Lévi-Strauss, C. (1955). Tristes Tropiques. (J. Weightman & D. Weightman, Trans.). Penguin. • Lévi-Strauss, C. (1963). Structural Anthropology. (C. Jacobson & B. G. Schoepf, Trans.). Basic Books. • Lévi-Strauss, C. (1964-1971). Mythologiques (Vols. 1-4). University of Chicago Press. • Lotman, Y. M. (1977). The Structure of the Artistic Text. (G. Lenhoff & R. Vroon, Trans.). University of Michigan Press. • Lotman, Y. M. (1990). Universe of the Mind: A Semiotic Theory of Culture. Tartu: Aleksandra. • Lotman, Y. M. (1990). Universe of the Mind: A Semiotic Theory of Culture. (A. Shukman, Trans.). Indiana University Press. • Peirce, C. S. (1931-1958). Collected Papers of Charles Sanders Peirce (Vols. 1-6). (C. Hartshorne & P. Weiss, Eds.). Harvard University Press. • Peirce, C. S. (1992-1998). The Essential Peirce: Selected Philosophical Writings (Vols. 1-2). (N. Houser & C. Kloesel, Eds.). Indiana University Press. • Propp, V. (1968). Morphology of the Folktale.(L. Scott, Trans.). University of Texas Press. • Ricoeur, P. (1970). Freud and Philosophy: An Essay on Interpretation. (D. Savage, Trans.). Yale University Press. • Ricoeur, P. (1984-1988). Time and Narrative (Vols. 1-3). (K. Blamey & D. Pellauer, Trans.). University of Chicago Press. • Saussure, F. de. (1916). Course in General Linguistics. (W. Baskin, Trans.). Dover Publications.